How Job Stress Affect Job Satisfaction and Employee Performance in Four-Star Hotels - Ni Made Dwi Puspitawati; Ni Putu Cempaka Dharmadewi Atmaja (AIBPM Publisher, 2021)
Four-Star Hotels in Bali continue to control the situation of the Covid-19 Pandemic by maintaining employee performance. Social Exchange Theory used to understand a person's behavior at work. A company leader who knows what employees want and can explain what will be obtained if the work results are in accordance with employee expectations will try to show maximum performance. The decline in employee performance indicates an increase in job stress and a decrease in employee job satisfaction. This study aims to determine the effect of job stress experienced by employee on job satisfaction and employee performance at Four-Star Hotels in Bali. The questionnaires were distributed to 130 employees from 10 Four-Star Hotels in Bali, only 117 questionnaires were returned (response rate 90%). The results showed that job stress has a negative effect on employee performance and, job satisfaction, while job satisfaction has no effect on employee performance. The research implies that job condition can cause stress depending on the employee's condition. The salaries they earn do not match the workload they, especially when working from home, and working time of other employees reduce their level of satisfaction at work. However, Covid-19 Pandemic conditions nowadays, employees feel that job satisfaction has no effect on their performance.